STUDY OF THE IMPACT OF KNOWLEDGE SECTIONS OF ELEMENTARY MATHEMATICS ON THE STUDY OF HIGHER MATHEMATICS IN ENGINEERING UNIVERSITIES - Gerasimenko, Petr; Khodakovskiy, Valentin; Verteshev, Sergey; Lyokhin, Sergey; Khvattcev, Alexander (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article presents the results of the study of the impact of knowledge sections of elementary mathematics on the study of higher mathematics by students of Pskov State University. The analysis is based on the knowledge of the elementary mathematics sections tested on a unified state exam (USE). The most important sections of USE's monitoring materials have been identified for the study. The results of these assignments are given to school leavers who have enrolled in 2018 and 2019 at Pskov State University. The regression analysis method examined the impact of USE results on higher mathematics by students studying at the university's technical areas. The regression rate, which indicates the strength of the link between the results of higher and elementary mathematics, is about 40%. Recommendations are made for the organization of the educational process of studying higher mathematics, taking into account the low level of knowledge of school mathematics entering the first year of the university